Radix natalensis: the effect of Fasciola hepatica infection on the reproductive activity of the snail - Dar, Yasser (EDP Sciences, 2014)
Experimental infections of Egyptian Radix natalensis (shell height at miracidial exposure: 4 mm) with a French isolate of Fasciola hepatica were carried out under laboratory conditions at 22 °C to specify the characteristics and follow the dynamics of their egg-laying. Controls constituted unexposed R. natalensis of the same size. No significant difference between controls and the uninfected snails of the exposed group was noted, whatever the parameter considered. In controls and exposed snails, the dates of the first egg masses were close to each other (56.4–65.3 days). In contrast, the life span of snails and the length of the egg-laying period were significantly shorter and egg production was significantly lower in infected R. natalensis than in controls and uninfected snails. In infected R. natalensis, but without cercarial shedding (NCS snails), egg production was irregular throughout the egg-laying period. In cercarial-shedding (CS) snails, the first egg masses were laid before the first cercarial emergence (at a mean of 56 days and 67 days, respectively). Thereafter, egg mass production of CS snails was irregular up to day 72 of the experiment, stopped during the following two weeks and started again after day 88 for a single snail. In conclusion, the F. hepatica infection of R. natalensis reduced the reproductive activity in both NCS and CS snails. The pattern noted for egg production in infected R. natalensis seems to be species-specific because of the high shell size of this lymnaeid and its role as an atypical intermediate host in the life cycle of the parasite.